Prevalence and prediction of occupational morbidities among male migrant workers in textile industries in Surat, India: a cross-sectional study - Maurya, Bharati (International Journal Of Community Medicine And Public Health, 2023)
Background: In the textile industry, male migrant workers from other Indian states predominate. Workers are more vulnerable to occupational hazards due to poor working conditions, such as long hours and workplace annoyances. These include noise, high temperatures, humidity, chemical fumes, and cotton or synthetic dust, which harm their health. This study investigated the morbidity patterns of textile migrant workers in Surat. Methods: From April to November 2017, cross-sectional research was conducted in three blocks, utilizing multistage stratified cluster sampling to survey 348 TMWs. A pre-tested and pre-designed structured questionnaire was developed to collect data on three types of textile units: yarn, weaving, and processing. A bivariate and binary logistic regression examined the relationship between the self-reported prevalence of occupational morbidities (outcome variables) and occupation-related factors (predictor variables). Results: Occupational morbidities affect 95% of workers. Self-reported morbidities include musculoskeletal morbidities (72.7%), respiratory morbidities (21.9%), ophthalmic morbidities (27.6%), skin morbidities (23.9%), and ENT problems (18.4%). Those working in weaving manufacturing units are 10% more likely to have ocular disorders (P<0.05). Those who engage in printing and dyeing processing units have a 27% higher chance of developing respiratory morbidities (P<0.05). Conclusions: The prevalence of occupational morbidity is significantly higher among textile workers. The hazardous risk factors responsible for these morbidities can be mitigated by improving working conditions and implementing suitable protective measures for textile workers. Intervention initiatives are required to address textile workers’ health concerns.